Orthodontic decompensation in skeletal Class III malocclusion: redefining the amount of movement assessed by Cone-Beam Computed Tomography - Cappellozza,José Antonio Zuega (2015)
Introduction:Cone-Beam Computed Tomography (CBCT) is essential for tridimensional planning of orthognathic surgery, as it allows visualization and evaluation of bone structures and mineralized tissues. Tomographic slices allow evaluation of tooth inclination and individualization of movement performed during preoperative decompensation. The aim of this paper was to assess maxillary and mandibular incisors inclination pre and post orthodontic decompensation in skeletal Class III malocclusion.Methods:The study was conducted on six individuals with skeletal Class III malocclusion, surgically treated, who had Cone-Beam Computed Tomographic scans obtained before and after orthodontic decompensation. On multiplanar reconstruction view, tomographic slices (axial, coronal and sagittal) were obtained on the long axis of each incisor. The sagittal slice was used for measurement taking, whereas the references used to assess tooth inclination were the long axis of maxillary teeth in relation to the palatal plane and the long axis of mandibular teeth in relation to the mandibular plane.Results:There was significant variation in the inclination of incisors before and after orthodontic decompensation. This change was of greater magnitude in the mandibular arch, evidencing that natural compensation is more effective in this arch, thereby requiring more intensive decompensation.Conclusion:When routinely performed, the protocols of decompensation treatment in surgical individuals often result in intensive movements, which should be reevaluated, since the extent of movement predisposes to reduction in bone attachment levels and root length.